Changes in retinal flow density measured by optical coherence tomography angiography in patients with carotid artery stenosis after carotid endarterectomy. Issue 1 (December 2018) - Lahme, Larissa; Marchiori, Elena; Panuccio, Giuseppe; Nelis, Pieter; Schubert, Friederike; Mihailovic, Natasa; Torsello, Giovanni; Eter, Nicole; Alnawaiseh, Maged
Abstract The aim of the study presented here was to evaluate retinal and optic nerve head (ONH) perfusion in patients with severe asymptomatic carotid artery stenosis (CAS) compared with healthy controls and to analyze the impact of carotid endarterectomy using optical coherence tomography angiography (OCT-A). 25 eyes of 25 patients with CAS (study group) and 25 eyes of 25 healthy controls (control group) were prospectively included in this study. OCT-A was performed using RTVue XR Avanti (Optovue, Inc, Fremont, California, USA). The flow density data in the superficial and deep retinal OCT-angiogram of the macula and in the radial peripapillary capillary network (RPC) of the ONH were extracted and analyzed. The flow density in the superficial retinal OCT angiogram of the macula and in the ONH were significantly lower in the study group compared with the control group (macula: p = 0.003) (ONH: p = 0.013). The flow density in the ONH improved significantly after carotid endarterectomy (p = 0.004). A reduced flow density was observed in patients with CAS when compared with healthy controls. The flow density also improved after carotid endarterectomy. Quantitative changes in the microvascular density, as measured using OCT-A, could well be useful in the diagnosis of CAS and the evaluation of therapy success.